Nuclear Deterrence in Europe Russian Approaches to a New Environment and Implications for the United States - Quinlivan, James T. (RAND Corporation, 2011)
Through a variety of policies and actions--and most recently in a new military doctrine adopted in February 2010--Russia has indicated the types of situations and threats that might cause it to resort to using nuclear weapons. This volume examines Russia's evolving framework for nuclear deterrence and its implications for U.S. military operations in Europe.